The effect of intermittent renewable supply on the forward premium in German electricity markets - Marius Paschen (University of Oldenburg, Department of Economics, 2016)
Renewable energy such as wind or solar power currently contributes a large share to the total German electricity supply as a result of the German energy transition. This paper presents an empirical analysis of how power shocks resulting from intermittent renewable supply affect forward premiums in German electricity markets. We contribute to the existing literature by investigating determinants of forward premiums, thereby focusing on wind and on solar power. We find positive wind shock effects on forward premiums. This can be explained as a consequence of the merit order effect. The findings in this paper underline the need to introduce wind power futures at the EEX to reduce the risk mark-up for participants in forward markets.
Keywords: Q42; Q41; C22; C51; 330; Electricity Market; Forward Premiums; Intermittent Wind; Solar Power